Bis(tetraphenylarsonium) hexachloridozirconate(IV) acetonitrile tetrasolvate - Rosendo Borjas (IUCrData, 2018)
The bis(tetraphenylarsonium) hexachloridozirconate(IV) salt, (AsPh4)2[ZrCl6] (Ph = C6H5), was prepared more than 25 years ago [Esmadi & Sutcliffe (1991). Indian J. Chem. 30 A, 99–101], but its crystal structure was never reported. By following a similar experimental procedure, the compound was synthesized and its crystal structure was investigated as a acetonitrile tetrasolvate, (As(C6H5)4)2[ZrCl6]·4CH3CN, by single-crystal X–ray diffraction. The [ZrCl6]2− anion adopts a slightly distorted octahedral coordination sphere, with Zr—Cl bond lengths of 2.4586 (6), 2.4723 (6), and 2.4818 (5) Å, and Cl—Zr—Cl angles ranging from 89.602 (19) to 90.397 (19)°.